ANALISIS PROFESIONALISME DAN INDEPENDENSI AUDITOR INTERNAL TERHADAP KUALITAS AUDIT PADA BPKP PROVINSI BENGKULU - Karnadi KArnadi; nina Yulianasari (Jurnal Ilmu Akuntansi, 2021)
This Study aims to determine the professionalism and independence analysis of audit quality at BPKP In Bengkulu Province. The regression equation obtained from the results of this study is as follows: Y=20,780 + 0,506 X1 + 0,050 X2. The coefficient of determination R2= 0,135. Value means that the variables of professionalism and independence are 13,5% while 86,5% is Influenced by other factors not examined. The t value > t Table (2,00856) on the effect of X1 on Y, the t value for the professionalism variable X1 is 3,166 with a sig value of 0,003 while the t table is 2,00856 with a sig value of 0,025% because t count> t table (3,166>2,00856) this indicates that H0 is accepted and it can be concluded that there is an effect of X1 on Y. the value of the variable t count > t table for the independent variable X2 is 0,147 with a sig value of 0,003 while the t table is 2,00856 with a sig value of 0,025 (2,5%) because t count < t table (0,147 < 2,00856) shows that H0 is rejected and it can be concluded that there is no effect of X2 on Y. The f value is 5,058 while the sig is 0,010. F table at the level of confidence is 3,18 this means that the value of f count > f table (5,058 > 3,18) which means that the variable professionalism (X1), Independence (X2) has a positive influence on the audit quality variable (Y) or collectively have simultaneous influence.